Preferred Orientation of TiN Coatings Enables Stable Zinc Anodes - Zheng, Jiaxian; Cao, Zhen; Ming, Fangwang; Liang, Hanfeng; Qi, Zhengbing; Liu, Wanqiang; Xia, Chuan; Chen, Cuixue; Cavallo, Luigi; Wang, Zhoucheng; Alshareef, Husam N (ACS energy letters, 2022)
Metallic Zn is considered as an ideal anode while its widespread use in rechargeable aqueous batteries still faces many challenges, mostly associated with the dendritic growth and corrosion of Zn and the side reactions. In this work, we demonstrate that a TiN protective coating layer with the preferential (200) orientation can effectively suppress both the Zn dendritic growth and side reactions; more interestingly, it can regulate the growth pattern of the byproduct (zinc hydroxide sulfate or ZHS) by inducing a lateral growth. As a result, reversible Zn plating/stripping over 2300 h at a practical current density of 1 mA cm–2 is achieved along with a nearly 100% Coulombic efficiency. This work not only establishes TiN (200) coatings as an effective Zn anode protective layer but also provides insights into the role of ZHS byproduct as well as strategies to inhibit side reaction and to regulate the growth pattern of ZHS.